Mengukur Relevansi Cashless Society pada Generasi Z - Permana, Gusi Putu Lestara; Apriani, Ni Kadek Mira (Penerbit Goodwood, 2025)
Purpose: This study aims to evaluate the relevance of a cashless society among Generation Z by employing the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The focus is to understand the factors influencing the acceptance and adoption of cashless payment systems within this demographic. Methodology/approach: The study was conducted in Denpasar City, targeting Generation Z individuals who reside there and have used digital wallet or e-wallet services. The sample size was determined using Hair’s formula, resulting in a total of 135 respondents. Results/findings: The findings suggest that the UTAUT model, particularly factors such as Behavioral Intention, Habit, and Social Influence, significantly affects the adoption of cashless payment methods. This indicates that user intention and habitual behavior are key drivers in embracing this technology. Conclusions: On the other hand, variables such as Awareness, Facilitating Conditions, Hedonic Motivation, Perceived Security, and Performance Expectancy did not show a significant influence on users’ behavioral intentions. This implies that, in the context of cashless payment adoption, social factors and habits are more influential than security concerns or performance expectations. Limitations: The study is limited to Generation Z, whereas cashless technology adoption is also growing among Millennials and Baby Boomers. Contribution: This study contributes to behavioral science, especially in the area of financial technology, and provides insights into the practical application of the UTAUT model.